2020
DOI: 10.1073/pnas.1919800117
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing by direct tagmentation of RNA/DNA hybrids

Abstract: Transcriptome profiling by RNA sequencing (RNA-seq) has been widely used to characterize cellular status, but it relies on second-strand complementary DNA (cDNA) synthesis to generate initial material for library preparation. Here we use bacterial transposase Tn5, which has been increasingly used in various high-throughput DNA analyses, to construct RNA-seq libraries without second-strand synthesis. We show that Tn5 transposome can randomly bind RNA/DNA heteroduplexes and add sequencing adapters onto RNA direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 42 publications
1
75
0
Order By: Relevance
“…Although the clinical verification has not been carried out yet, this technology, once proved, might be conducive to rapid diagnosis of the disease [43]. A research group of Peking University claimed to have developed a new method for rapid construction of transcriptome sequencing library of SHERRY, which is helpful for rapid sequencing of SARS-CoV-2 [44]. found that chloroquine has an immune-modulating activity and could effectively inhibit in this virus in vitro [46] .…”
Section: Diagnosis Of Sars-cov-2mentioning
confidence: 99%
“…Although the clinical verification has not been carried out yet, this technology, once proved, might be conducive to rapid diagnosis of the disease [43]. A research group of Peking University claimed to have developed a new method for rapid construction of transcriptome sequencing library of SHERRY, which is helpful for rapid sequencing of SARS-CoV-2 [44]. found that chloroquine has an immune-modulating activity and could effectively inhibit in this virus in vitro [46] .…”
Section: Diagnosis Of Sars-cov-2mentioning
confidence: 99%
“…Current real-time RT-PCR techniques are not convenient, rapid, robust and also not 100% accurate (high rate of false negative). Furthermore, these methods (SHERRY), which is helpful for rapid sequencing of SARS-CoV-2 (Di et al, 2020). They showed that Tn5 transposase, which randomly binds and cuts double-stranded DNA, can directly fragment and prime the RNA/DNA heteroduplexes generated by reverse transcription.…”
Section: Diagnostic Tools For the Covid-19mentioning
confidence: 99%
“…Currently, the most comprehensive strategy is the combination of metatranscriptomics profiling with post-library SARS-CoV-2 target enrichment( 6 ). However, in most conventional RNA-seq methods, the double-strand DNA ligation (dsDL) portion of the protocol is usually the most demanding on hands-on time and user technique( 7 ). When superimposed on the target enrichment process, these labor intensive and lengthy protocols become impractical for routine use in the clinic, much less for the timely monitoring of viral genetics and evolution on large volumes of samples during an outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a new RNA-seq library construction strategy that aims to address some of these challenges: SHERRY avoids the problematic dsDL step in library construction by taking advantage of the newly discovered Tn5 tagmentation activity on RNA/DNA hybrids, to directly tag RNA/cDNA fragments with sequencing adapters ( 7 ). As such, SHERRY has minimal sample transfers and greatly reduced hands-on time, making it simple, robust, and suitable for inputs ranging from single cells to 200 ng total RNA.…”
Section: Introductionmentioning
confidence: 99%